The effects of corrective gymnastics on the postural status of the spine in the frontal plane in preschool children - Aleksandar Miletić; Zoran Milić; Dejan Savićević; Darijan Ujsasi (Exercise and Quality of Life)
Postural irregularities, i.e., deviations from normal posture, are a growing problem today. Physical inactivity in preschool children can lead to some physiological changes, which, if not remedied timely, tend to more seriously impair health in later stages of life. Muscle activity caused by biomechanical adaptation to certain body positions in a sedentary regime in children can form muscle asymmetries. The study aimed to determine the effects of corrective gymnastics on the postural status of the spine in the frontal plane in preschool children. The total sample of children (n=133; AGE: 6.2±0.6) was divided into three sub-samples: experimental group E1 – 45 (25.57%), experimental group with additional exercises E2 – 45 (25.57%) and control group C-43 (48.86%). This is a longitudinal-type study that involved the application of a ten-week corrective gymnastics intervention on children aged 5 to 7 from Subotica, who participated in the formation of the sample. Based on the analysis of the results of the multivariate analysis of variance it can be concluded that there are no statistically significant differences (P=0.17) between the subjects from the experimental groups and the control group in the variables used for assessment of the spinal column in the frontal plane, and it is necessary to extend the treatment time in preschool children when corrective gymnastics is applied to changes in postural status when it is observed in the frontal plane.